Selective thyroid hormone receptor β agonists with oxadiazolone acid isosteres. Issue 21 (1st November 2020) - Kirschberg, Thorsten A.; Jones, Christopher T.; Xu, Yingzi; Fenaux, Martijn; Halcomb, Randall L.; Wang, Yujin; Klucher, Kevin
Graphical abstract: Abstract: Use of the oxadiazolone acid isostere in triiodothyronine analogs yielded potent and selective agonists for the thyroid hormone receptor β. Selected examples showed good in-vivo efficacy in a rat hypercholesterolemic model. One compound was further profiled in a diet-induced mouse model of nonalcoholic steatohepatitis (NASH) and showed robust target engagement and significant histological improvements in both liver steatosis and fibrosis.